2018
DOI: 10.1590/1806-9282.64.04.361
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of TOLL-like receptor 4 (TLR-4) and matrix metalloproteinase 9 (MMP-9)/Tissue inhibitor of metalloproteinase 1 (TIMP-1) in pulmonary blood vessels with chronic obstructive pulmonary diseases and their relationships with pulmonary vascular remodelling

Abstract: The upregulation of TLR-4 in the pulmonary arterial smooth muscle cells of COPD patients could promote the inflammations and the MMP-9 expression, thus causing abnormal degradation of extracellular matrix, so it played an important role in the process of PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…TGF-β1 has been proven to protect the aorta and other blood vessels from damage caused by factors such as high blood pressure and high cholesterol [18,19]. Researches have shown that MMP-9 and TGF-β1 play vital roles in pulmonary vascular remodeling [14,20,21]. Study showed that the enhanced TGF-β-driven smad-2/3 signaling promoted pulmonary vascular remodeling in inflaming lungs [22].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 has been proven to protect the aorta and other blood vessels from damage caused by factors such as high blood pressure and high cholesterol [18,19]. Researches have shown that MMP-9 and TGF-β1 play vital roles in pulmonary vascular remodeling [14,20,21]. Study showed that the enhanced TGF-β-driven smad-2/3 signaling promoted pulmonary vascular remodeling in inflaming lungs [22].…”
Section: Introductionmentioning
confidence: 99%